Lower Jurassic dolomite-limestone succession with coal in the Kočevski Rog and correlation with neighbouring areas (southeastern Slovenia) - Dozet, Stevo (Geologija, 1998)
The article deals with the Lower Jurassic shallow-water succession of carbonate rocks with lenses of coal in the area of the Dinaric carbonate platform east of Kočevje. The coal is of Middle Liassic age. The footwall of the coal is represented by the Lower Liassic grained bituminous dolomite and the hanging wall by the Upper Liassic spotted limestone. The coal was formed in a shallow lagoon and/or deeper marsh at paralic-limnic conditions. A correlation of developments of the Liassic beds in the Kočevski Rog, Suha krajina, Mala gora, Kočevska Mala gora and Bela krajina area has been performed in this paper as well.